2014
DOI: 10.1002/vnl.21380
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nano-CeO2as Co-stabilizer on the thermal stabilization efficiency of novel calcium/Zinc soap stabilizers for poly(vinyl chloride)

Abstract: The novel organic calcium (Ca)/zinc (Zn) stabilizer of poly(vinyl chloride) (PVC) was synthesized from poly (zinc methylacrylate) and Ca adipate. The influences of Zn/Ca soap weight ratios and nano‐CeO2 as co‐stabilizer on the thermal stability of PVC were investigated. Congo red testing, thermogravimetric analysis, dynamic rheology, and dynamic mechanical analysis of the mixtures were performed. The results show that the novel stabilizer has good stabilization efficiency on PVC. When 5 phr (parts by weight pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The reason is that there are good synergy effect between ZnOr 2 and CaSt 2 , which can efficaciously enhance the thermal stability of PVC. For another, Figure 9 also shows similar testing results: that the thermal stability time of PVC/ZnSt 2 /CaSt 2 was increased with the increasing of CaSt 2 concentration [3,35]. By comparing Figure 8 and Figure 9, it can be confirmed that ZnOr 2 displays a better stabilizing effect for PVC than the commercial thermal stabilizer ZnSt 2 .…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The reason is that there are good synergy effect between ZnOr 2 and CaSt 2 , which can efficaciously enhance the thermal stability of PVC. For another, Figure 9 also shows similar testing results: that the thermal stability time of PVC/ZnSt 2 /CaSt 2 was increased with the increasing of CaSt 2 concentration [3,35]. By comparing Figure 8 and Figure 9, it can be confirmed that ZnOr 2 displays a better stabilizing effect for PVC than the commercial thermal stabilizer ZnSt 2 .…”
Section: Resultssupporting
confidence: 55%
“…Hence, in order to create more high-efficiency and eco-friendly thermal stabilizers, it should be integrated with other stabilizers (metal soap, auxiliary stabilizers, etc.) to manufacture complex thermal stabilizers [3,35]. This study includes an investigation of choosing calcium stearate (CaSt 2 ) as a traditional metal soap stabilizer, with DBM and PER as auxiliary thermal stabilizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal soaps are the most common thermal stabilizers for PVC. Because the calcium (Ca) soap and zinc (Zn) soap are relatively safe thermal stabilizers for PVC, the United States Food and Drug Administration states that Ca/Zn soap stabilizer is a nontoxic additive [9]. Calcium stearate/zinc stearate (CaSt 2 /ZnSt 2 ), for example, is widely used in food packaging materials, children's toys, and bottle seals because of its nontoxic property.…”
Section: Introductionmentioning
confidence: 99%
“…As we known, the initial antidiscoloration ability of zinc stearate is very good and has good synergistic effect with calcium stearate and PE. [ 10,11 ] So mixed rare earth stabilizer with them can change the defect of the single stabilizer.…”
Section: Introductionmentioning
confidence: 99%